PENGEMBANGAN MODEL SISTEM INFORMASI MANAJEMEN PENDIDIKAN (RESEARCH AND DEVELOPMENT) PADA PROGRAM STUDI MAGISTER MANAJEMEN PENDIDIKAN PASCASARJANA UNIVERSITAS NEGERI JAKARTA - Ary Susanto (Jurnal Manajemen Pendidikan, 2012)
This study aims to analyze needs, plan, develop, and test a model of management information systems at the Department of Master of Educational Management, Post Graduate Studies State University of Jakarta. This study used a qualitative approach. The method used is the research and development. Researchers developed a model of driver's license through the ten steps (borg and Gall) were then categorized into four stages (the initial data collection and needs analysis, planning, development, and testing). Data collected and analyzed in a qualitative (Creswell). Through the process of library research, observation, interviews, and documentation study obtained data on student opinion of the service of information, setting conditions, and analysis of information system requirements on the Department. The results showed that the system is still used convensional information and technology-based information system is needed. In the testing phase the chairman of the Department declared feasible for use. From the results obtained, conclude that the management of data and infoemation is still conventional, technology-based information system is needed, planning and development accordance with aspects of management education in the Departement, and the products have passed testing by the Chairman. Provision of human resources, tools, policy support, and student participation is an important factor for the development of subsequent systems